Predators and losses of farm animals - Lundsten, Joakim; Rapp, Edvin (2016)
Bounties have been a widely used method of wildlife management, especially for predators. Bounties were used by ancient Greeks and are still used frequently around the world. Despite this, there are few quantitative evaluations of the methods efficiency. In this study our goal was to test the hypothesis that bounties are effective by analyzing historical data from 1876 to 1930 in Sweden. We tested if the total amount of paid bounties reduced the economic losses of farm animals killed by predators. We also tested if the number of bears (Ursus arctos arctos L.), wolves (Canis lupus L.) and lynx (Lynx lynx L.) killed caused a decrease in the amount of sheep (Ovis aries L.) killed. Our hypothesis was that these factors would not have a significant effect and it was supported by our results. Many authors have been skeptical towards the efficiency of bounties, and there many potential flaws like fraud. Another problem with this economical motivation for hunting is that when the population decreases, large bounties are needed for hunters to keep the population from recovering. Even though bounties have often failed in controlling populations, people seem to forget these mistakes resulting in more resources being wasted. Our analysis suggests that the bounty system has had no significant effect on the economic loss caused by predation on farm animals in Sweden. The results also supported the hypothesis that the number of bears, lynx and wolves killed did not affect the number of sheep killed.